TRPC4 regulates limbic behavior and neuronal development by stabilizing dendrite branches through actomyosin-driven integrin activation - Jeon, Jaepyo; Moore, Travis I.; So, Insuk; Freichel, Marc; Flockerzi, Veit; Birnbaumer, Lutz; Zhu, Michael X. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Transient Receptor Potential Canonical 4 (TRPC4) channels have been implicated in multiple neurological functions, including anxiety and sociability. TRPC4 variants were also found in patients with autism. However, the contributions of TRPC4 to neurodevelopment remain undefined. Here, we show that neurobehavioral deficits appear early in young TRPC4 knockout (Trpc4−/−) mice immediately after weaning, manifesting as alterations in multiple, limbic-related behaviors, such as nesting, marble burying, burrowing, self-grooming, and social interactions. Hippocampal neurons of Trpc4−/− mice exhibit reduced dendritic arborization both in vivo and in vitro. Mechanistically, we found that TRPC4 expression in dendrites surged at the same time when glutamate exerted its stimulatory effect on dendritic branching. In live-cell imaging assays, glutamate induced the formation of new dendrite branches in both wild-type and Trpc4−/− neurons. However, many of the new and preexisting branches retracted in the mutant neurons. Furthermore, TRPC4 mediated Ca2+ entry in dendrites downstream from metabotropic glutamate receptors, leading to phosphorylation of nonmuscle myosin light chain (MLC) by the Ca2+-dependent myosin light chain kinase (MLCK), which in turn supported integrin activation in dendrite branches. Our findings underscore the essential role of TRPC4 channels in both dendrite morphogenesis and modulation of motivation-related behaviors. The mechanistic underpinning elucidated for the impaired dendritic development and abnormal behaviors in juvenile Trpc4−/− mice provides insights into the understanding of neurodevelopmental disorders, particularly autism spectrum disorder, opening potential avenues for targeted therapeutic interventions against TRPC4.